Investigating the effect of nanorefrigerants on a heat pump performance and cost-effectiveness. (October 2019) - Kosmadakis, George; Neofytou, Panagiotis
Highlights: Detailed heat pump numerical model including the effect of nanoparticles. Investigation of heat pump performance with different nanorefrigerants. Heat transfer and pressure drop effects of nanorefrigerants. COP increases up to 6% with nanorefrigerants at both heating and cooling modes. The payback period can be as long as 6 years, having large uncertainty. Abstract: The use of nanoparticles in vapour compression heat pumps introduces some interesting features, such as heat transfer enhancement during boiling and condensation. To gain a better understanding of the related processes and potential, a detailed thermodynamic model is developed considering different nanorefrigerants. Suitable refrigerants (R134a and R1234yf) and nanoparticles (Cu, Al2 O3, and CuO) are screened and following the model validation, an extensive analysis of the heat pump operation at both heating and cooling modes is conducted for a variable nanoparticle mass fraction from 0 up to 5%. An increase of the COP of up to 5–6% is found at both modes, and is mostly attributed to the cooling effect of the nanoparticles during the compression. The heating and cooling capacities were almost constant, as direct outcome of the numerical methodology, while the compressor consumption decreased. Subsequently, both the heat transfer and pressure drop processes are examined, showing that the heat transfer coefficients are increased by up to 6% mainly during boiling and condensation, while the total pressure drop is increased by up to 3.5%. The final step was to conduct a preliminary cost analysis of the use of nanoparticles in heat pumps, resulting to a 6-year payback period that can be shortened to 2.5 years under favourable conditions.